The Microstructure of Fear, the Fama–French factors and the Global Financial Crisis of 2007 and 2008 - Lim, D.; Durand, Robert; Yang, J. (Elsevier BV, North-Holland, 2014)
We analyze minute by minute equity price data from 1 August 2005 to 31 October 2008 to study the relationship between the three sources of systematic risk in Fama and French's (1993) model and the market's expectation of total risk as represented by the VIX (the “fear factor”). Our findings confirm the predicted relationship between the equity risk-premium and risk (Merton, 1980).We find that the size-premium is driven by investors who are flying-to-quality (Abel, 1988; Barsky, 1989). We also find that investors became increasingly sensitive to changes in the VIX during the global financial crisis.